Bi‐allelic loss of ERGIC1 causes relatively mild arthrogryposis. Issue 3 (14th June 2021) - Marconi, Caterina; Lemmens, Laure; Masclaux, Frédéric; Mattioli, Francesca; Fluss, Joël; Extermann, Philippe; Mendez, Purificacion; Leuchter, Russia Ha‐Vinh; Stathaki, Elissavet; Laurent, Sacha; Hammar, Eva; Vannier, Anne; et al.
Abstract: Arthrogryposis describes the presence of multiple joint‐contractures. Clinical severity of this phenotype is variable, and more than 400 causative genes have been proposed. Among these, ERGIC1 is a recently reported candidate encoding a putative transmembrane protein of the ER‐Golgi interface. Two homozygous missense variants have been reported in patients with relatively mild non‐syndromic arthrogryposis. In a consanguineous family with two affected siblings presenting congenital arthrogryposis and some facial dysmorphism we performed prenatal array‐CGH, postnatal targeted exome and genome sequencing. Genome sequencing identified a homozygous 22.6 Kb deletion encompassing the promoter and first exon of ERGIC1 . mRNA quantification showed the complete absence of ERGIC1 expression in the two affected siblings and a decrease in heterozygous parents. Our observations validate the pathogenic role of ERGIC1 in congenital arthrogryposis and demonstrate that complete loss of function causes a relatively mild phenotype. These findings will contribute to improve genetic counseling of ERGIC1 mutations. Abstract :